Thermal reactions involving 1-azadienes and allenic esters-(II):1a reactions of 3-(N-aryliminomethyl)chromones with allenic esters-tandem reorganization of [2+2] cycloadducts to novel compounds. Issue 33 (12th August 2015) - Kapur, Ashish; Sharma, Vishal; Kaur, Amandeep; Parashar, Poonam; Kanwal, Priyanka; Gupta, Vivek; Ishar, Mohan Paul S.
Graphical abstract: Abstract: Thermal reactions of 3-( N -aryliminomethyl)chromones (4a –d ) with ethyl 2, 3-butadienoate (5a ) and ethyl 4-phenyl-2, 3-butadienoate (5b ), on refluxing in dry benzene, afford novel compounds6a –e, apparently, derived from tandem reorganization of initially formed [2+2] cycloadducts. However, reaction of4a, d with ethyl 2, 3-pentadienoate (5c, R = CH3 ) under similar condition follows a different course yielding novel molecules7a, d and8a, d . Plausible mechanistic rationale for the formation of new molecules is proffered.